KESADARAN (AWARENESS) DAN PEMAHAMAN (UNDERSTANDING) AKUNTAN PENDIDIK TERHADAP XBRL - Yusti Pujisari; Frasto Biyanto (INVENTORY: JURNAL AKUNTANSI, 2019)
XBRL is a global standard that enables financial information to be analyzedquickly, cheaply, and easily and increases access by users. Since 2015 Indonesia Exchange (IDX) has encouraged companies in Indonesia to adopt XBRL for their  financial report. XBRL format made by IDX called IDX Taxonomy 2014. The adoption of XBRL in company financial report finally has an impact to the accounting education. This is because reducing and eliminating the gap between accounting education and accounting practice must always be sought. The purpose of this study is to explore the awareness and understanding  of  accounting educators in Indonesiaabout XBRL.Accounting educators are the profession which have responsibility in accounting education development. There were 124 accounting educators as a sample from several universities in Indonesia. The questionnaires were used to obtain the data, which distributed via email and social media. The results show that most of accounting educators do not aware and understand about what XBRL is. However, they who have not know about XBRL yet, has a curiosity and want to learn more about XBRL.